INDIA’S STRATEGIC RESET IN RELATIONS WITH MOZAMBIQUE : BILATERAL TRADE RELATIONS - Antony Jeyakumar J; Dr. M. Abdul Jamal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The relationship between India and Mozambique has a long history of friendly ties that have been built upon traditional linkages dating back to several centuries. That has been further strengthened in recent decades, to foster the economic and social status of both the regions. Since 2004, bilateral trade between both the countries have seen an uptrend which has increased from US 111 million in 2004 to US 4.03 billion in 2023. The availability of abundant natural and mineral resources sets Mozambique to seek a significant growth in the economy using trade as an instrument. The bilateral trade between India and Mozambique had benefitted both the countries equally and its very obvious in the case of Mozambique which has recorded an average of 5 percent of growth in the GDP annually, having India as its leading trade partner. The benefits reaped by both the nations in sharing their resources has been proved from analysing the two decades of trade history between two regions.